Analisis Dampak Pelaksanaan Pengembangan Usaha Agribisnis Pedesaan (PUAP) Terhadap Pendapatan Anggota Gapoktan Mekar Mulyo, Kelurahan Gadang, Kota Malang - Nur Ocvanny Amir; Rahmad Pulung Sudibyo (Universitas Muhammadiyah Malang, 2018)
One of the government's efforts in alleviating the poverty of rural residents who are living in the agricultural sector is the Rural Agribusiness Development Program (PUAP). Gapoktan Mekar Mulyo, Gadang Village, Malang City is one of the recipients of business capital assistance. This study aims to 1) find out the technical implementation of PUAP fund distribution activities in Gapoktan Mekar Mulyo, 2) Analyze the impact of PUAP implementation on the income of borrowing members in Gapoktan Mekar Mulyo. This research was carried out in Gapoktan Mekar Mulyo, Gadang Village, Malang City in January - October 2018. Sampling in this study used census method. The analytical method used is cost analysis, revenue, income and analysis of Paired Samples T Test to analyze the impact of the PUAP program on the income of Gapoktan members. The results of this study include: 1) Technical implementation of PUAP fund distribution activities in Gapoktan Mekar Mulyo started from Gapoktan to submit proposals to the Ministry of Agriculture of Indonesia, selection of PUAP Gapoktan proposals, proposals that passed the selection to get PUAP BLM Rp. 100.000.000, - which is transferred directly to Gapoktan account, then deliberation on the use of funds according to the proposal, the funds are distributed to each farmer group that has been adjusted to the Business Plan of Members (RUA) of the Farmers Group, 2) There is the impact of PUAP implementation on income borrowing members of funds in Gapoktan Mekar Mulyo, where the income of Gapoktan members after receiving the PUAP program is greater than the income of Gapoktan members before receiving the PUAP program.